Influência da temperatura de transporte de ovários na maturação in vitro de oócitos caninos coletados em diferentes estágios do ciclo estral - Pereira, Leda Maria Costa [UNESP]; De Bersano, P. R. [UNESP]; Lopes, Maria Denise [UNESP] (My University, 2015)
This study evaluated the influence of estrous cycle stage and transport temperature of ovaries on in vitro maturation of canine oocytes. The bitches were categorized into two groups based on stage of estrus cycle: diestrus or anestrus. One ovary of each pair collected was transported in saline solution at 4°C while the other was transported at 37°C. Thus, ovarian tissue was sliced in PBS to release cumulus oocyte complexes (COCs). A total of 345 COCs (n = 186 oocytes from ovaries of bitches in anestrus and 159 in diestrus) were cultivated in TCM 199 supplemented with HEPES, sodium pyruvate, cysteine, follicle stimulating hormone (FSH), human chorionic gonadotropin (hCG), estrogen (E2) and epidermal growth factor (EGF). After 72h of maturation, the COCs were denuded, fixed and stained to assess nuclear maturation. The Fisher test was applied to examine the differences between the groups. The significance level adopted was 0.05. The oocytes obtained from the ovaries from bitches in diestrus transported at 4°C shown increased frequency of oocytes in metaphase II stage than those maintained at 37°C (p < 0.01). Similarly, there was increased frequency of oocytes in metaphase II (11.1%) stage from the ovaries of bitches in anestrus and transported at 4°C, than those maintained at 37°C (p < 0.05). It was concluded that transport temperature influences the results of canine oocyte viability and in vitro maturation, regardless of reproductive stage of the female.
Effect of transport temperature of ovaries on in vitro maturation of canine oocytes collected in different stages of the estrous cycle
Keywords: Anestrus; Bitch; Diestrus; In vitro maturation; Temperature